Pengukuran Beban Kerja pada Karyawan Non Organik Grup A di PT XYZ dengan Metode SOFI dan SDS (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2026)
The most valuable asset of a company is its employees due to their performance. The performance of PT. XYZ in recent times has tended to decline due to the heavy workload on Group A non-organic employees, which has resulted in reduced employee productivity. This study aims to determine the workload value and the level of fatigue experienced by Group A non-organic employees at PT. XYZ using the SOFI and SDS methods. It also aims to recommend efforts to reduce the workload and stress levels for Group A non-organic employees at PT. XYZ. This study is a descriptive qualitative research using interview methods and distributing questionnaires to 18 non-organic employees of group A. The results of the study indicate that the analysis of workload (fatigue) measurement using the SOFI method obtained a physical fatigue level among non-organic employees of group A at PT. XYZ with an average total score of 4.61, which means that the employees experienced a workload (fatigue) level categorized as moderate. Meanwhile, the analysis of work stress measurement using the SDS method obtained an average total score of 14, indicating that the stress level among non-organic employees of group A at PT. XYZ falls in the moderate category.